2011
DOI: 10.1158/1535-7163.mct-11-0252
|View full text |Cite
|
Sign up to set email alerts
|

Trabectedin and Its C Subunit Modified Analogue PM01183 Attenuate Nucleotide Excision Repair and Show Activity toward Platinum-Resistant Cells

Abstract: PM01183 is a novel marine-derived covalent DNA binder in clinical development. PM01183 is structurally similar to trabectedin (yondelis, ecteinascidin-743) except for the C subunit, and this modification is accompanied by different pharmacokinetics in cancer patients. We here characterize the interaction of PM01183 with the nucleotide excision repair (NER) pathway in comparison with trabectedin. Our results show for the first time that although neither PM01183 nor trabectedin is repaired by NER, both compounds… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 40 publications
3
53
0
Order By: Relevance
“…For instance, the synthetic agent lurbinectedin or PM01183 (72), which was obtained by modification of the subunit C of 71, showed a potent cytotoxic activity against tumor cell line of different origin, and it was introduced in phase I clinical trials for solid tumor, and phase II for metastatic pancreatic cancer. PM01183 (72) showed enhanced activity to cisplatin-and oxaliplatin-resistant cell line, and combination of 72 and cisplatin was the most synergistic toward parental and cisplatin-resistant ovarian carcinoma cells [153]. Figure 13) is an anticancer tetrahydroisoquinolone alkaloid already approved by the FDA.…”
Section: Ecteinascidin 743 (Trabectedin) and Derivativesmentioning
confidence: 99%
“…For instance, the synthetic agent lurbinectedin or PM01183 (72), which was obtained by modification of the subunit C of 71, showed a potent cytotoxic activity against tumor cell line of different origin, and it was introduced in phase I clinical trials for solid tumor, and phase II for metastatic pancreatic cancer. PM01183 (72) showed enhanced activity to cisplatin-and oxaliplatin-resistant cell line, and combination of 72 and cisplatin was the most synergistic toward parental and cisplatin-resistant ovarian carcinoma cells [153]. Figure 13) is an anticancer tetrahydroisoquinolone alkaloid already approved by the FDA.…”
Section: Ecteinascidin 743 (Trabectedin) and Derivativesmentioning
confidence: 99%
“…Indeed, it is possible that this part of the molecule interacts directly with TC-NER factors and could interfere with the repair mechanism. In this sense, lurbinectedin is able to attenuate the repair of specific nucleotide excision repair (NER) substrates (17,18). In addition to its activity in tumor cells, it was recently shown that lurbinectedin affects the inflammatory microenvironment, with a selective apoptotic-inducing effect on mononuclear phagocytes and a specific inhibition of production of inflammatory cytokines (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…PM01183 (lurbinectedin, 103, Figure 11) is another very promising synthetic analog of ET 743; it is structurally similar to ET 743 except for the C subunit, where the tetrahydroisoquinoline present in ET 743 is replaced by a tetrahydro β-carboline in PM01183 [97]. This structural variation is accompanied by important modification of pharmacokinetic and pharmacodynamic properties in cancer patients [75,98]. Like ET743, PM01183 covalently binds to the minor groove of the DNA-forming DNA adducts, which give rise to double strand breaks and perturbations of the cell cycle inducing cell death.…”
Section: 'mentioning
confidence: 99%
“…PM01183 is also undergoing Phase I development in combination with other chemotherapies and in hematological tumors. On August 20, 2012, PharmaMar received FDA orphan drug designation (ODD) for PM01183 for the treatment of ovarian cancer [98,99]. Pyridoacridine alkaloids display diverse biological activities including cytotoxicity, production of reactive oxygen species (ROS), and topoisomerase inhibition.…”
Section: 'mentioning
confidence: 99%